Diagnosis of Glaucoma by Indirect Classifiers - Peters, A.; Lausen, B.; Michelson, G.; Gefeller, O. (Methods of Information in Medicine, 2003)
Objectives: Demonstration of the applicability of a framework called indirect classification to the example of glaucoma classification. Indirect classification combines medical a priori knowledge and statistical classification methods. The method is compared to direct classification approaches with respect to the estimated misclassification error.Methods: Indirect classification is applied using classification trees and the diagnosis of glaucoma. Misclassification errors are reduced by bootstrap aggregation. As direct classification methods linear discriminant analysis, classification trees and bootstrap aggregated classification trees are utilized in the problem of glaucoma diagnosis. Misclassification rates are estimated via 10-fold cross-validation.Results: Indirect classification techniques reduce the misclassification error in the context of glaucoma classification compared to direct classification methods.Conclusions: Embedding a priori knowledge into statistical classification techniques can improve misclassification results. Indirect classification offers a framework to realize this combination.
Keywords: Glaucoma; classification; decision trees